Novel GLP-1 Analog Supaglutide Stimulates Insulin Secretion in Mouse and Human Islet Beta-Cells and Improves Glucose Homeostasis in Diabetic Mice - Ren, Liwei; Cui, Qiaoli; Liu, Wenjuan; Wang, Liqian; Liao, Yijing; Feng, Ying; Sun, Wanwan; Yang, Yehong; Zhang, Zhaoyun; Jin, Tianru; Prud’homme, Gerald J.; Zhang, Lina; et al. (Frontiers in Physiology, 2019)
Glucagon-like peptide-1(GLP-1), an incretin hormone plays an important role in regulating glucose homeostasis. The therapeutic use of native GLP-1 is inadequate due to its short in vivo half-life. We recently developed a novel GLP-1 mimetics supaglutide, and demonstrated that this formulation retained native GLP-1 biological activities and possessed long-lasting GLP-1 actions. In this study, we further examined its abilities in regulating blood glucose in diabetic mice. We found that supaglutide stimulated insulin secretion in both mouse and human islets in a dose-dependent fashion. Oral glucose tolerance test conducted in normal ICR mice showed that supaglutide significantly decreased postprandial glucose excursions in a dose-dependent fashion. In type 2 diabetic db/db mice, a single-dose injection of supaglutide significantly decreased blood glucose levels, and this efficacy was lasted for at least 72 h in a dose-dependent fashion. During a 4-week intervention course supaglutide (twice injections per week) dose-dependently and significantly decreased fasting and random blood glucose levels in hyperglycemic db/db mice. Supaglutide, at a dose of 1.2 mg/kg, significantly reduced serum fructosamine levels. This was associated with significant enlargement of beta-cell mass, increased pancreatic insulin content, and increased plasma insulin level. Notably, during the intervention course supaglutide significantly reduced body-weight gain in these obese diabetic mice, associated with reduced fat mass (but not the lean mass), improved lipid profile, i.e., declined serum triglyceride, and free fatty acid levels compared to the placebo control. These finding reveals that supaglutide exerts beneficial effects in regulating blood glucose and lipid homeostasis in diabetic db/db mice.